Conducting composite materials from the biopolymer kappa-carrageenan and carbon nanotubes - Aldalbahi, Ali; Chu, Jin; Feng, Peter; in het Panhuis, Marc (Beilstein Journal of Nanotechnology, 2012)
Conducting composite films containing carbon nanotubes (CNTs) were prepared by using the biopolymer kappa-carrageenan (KC) as a dispersant. Rheological studies indicated that 0.5% w/v was the appropriate KC concentration for dispersing CNTs. Our results showed that multiwalled nanotubes (MWNTs) required less sonic energy than single-walled nanotubes (SWNTs) for the dispersion process to be complete. Films prepared by vacuum filtration exhibited higher conductivity and improved mechanical characteristics compared to those prepared by evaporative casting. All composite films displayed sensitivity to water vapour, but MWNT films were more sensitive than SWNT films.
Keywords: biopolymers; carbon nanotubes; carrageenan; composite materials; conductivity; mechanical; rheology